Differences in social support based on demographic factors among university students during the covid-19 pandemic - Norsimah Dasan; Balan Rathakrishnan; Muhammad Idris Bullare @ Bahari; Lailawati Madlan @ Endalan; Norkiah Arsat (Fakulti Psikologi dan Pendidikan, 2021)
The Covid-19 pandemic has led to the emergence of a new norm among university students. The movement control command for breaking the Covid-19 chain has resulted in the online platform being fully used by instructors to deliver courses to students. Meanwhile, students also need to make sure active participate in the new teaching and learning environment and at the same time adhere to the SOPs which have been set. Accordingly, social support is assumed to play an important role in ensuring the continuity of the role of university students in completing academic assignments as well as socially responsible individuals. Social support is categorized into 3 important aspects namely family support, peer support, and significant individual support to student This study was to identify the differences of these three social supports based on the student’s place of residence during the pandemic period and the student’s gender. A quantitative study was conducted by survey method on 590 samples of University Malaysia Sabah students who were selected at simple random. The instrument used is the Multidimensional Scale of Perceived Social Support (MSPSS). The results of the study found that peer support had significant differences based on where students lived during a pandemic. Meanwhile, family support, and significant individual support, did not show significant differences. Moreover, family support, peer support, and significant individual support had no significant differences based on student gender. The implications of this study can offer new advice to the field of psychology especially in increasing social support during pandemic periods. University authorities and policymakers can use the statistics of this study for the construction of appropriate new modules or programs.